Author Correction: Carbon budgets for 1.5 and 2 °C targets lowered by natural wetland and permafrost feedbacks. Issue 11 (November 2018) - Comyn-Platt, Edward; Hayman, Garry; Huntingford, Chris; Chadburn, Sarah; Burke, Eleanor; Harper, Anna; Collins, William; Webber, Christopher; Powell, Tom; Cox, Peter; Gedney, Nicola; Sitch, Stephen
In the version of this Article originally published, a parallelization coding problem, which meant that a subset of model grid cells were subjected to erroneous updating of atmospheric gas concentrations, resulted in incorrect calculation of atmospheric CO2 for these grid cells, and therefore underestimation of the carbon uptake by land through vegetation growth and eventual increases to soil carbon stocks. Having re-run the simulations using the corrected code, the authors found that the original estimates of the impact of the natural wetland methane feedback were overestimated. The permafrost and natural wetland methane feedback requires lower permissible emissions of 9–15% to achieve climate stabilization at 1.5 °C, compared with the original published estimate of 17–23%. The Article text, Table 1 and Fig. 3 have been updated online to reflect the revised numerical estimates. The Supplementary Information file has also been amended, with Supplementary Figs 6, 7, 8 and 9 replaced with revised versions produced using the corrected model output. As the strength of feedbacks remain significant, still require inclusion in climate policy and are nonlinear with global warming, the overall conclusions of the Article remain unchanged.